The mummy [videorecording (Blu-Ray)] - Sommers, Stephen; Sommers, Stephen; Fraser, Brendan, 1968-; Weisz, Rachel, 1970-; Hannah, John, 1962-; Vosloo, Arnold (Universal Pictures Home Entertainment, 2017)
Deep in the Egyptian desert, a handful of adventurers searching for a long-lost treasure have just unearthed a 3,000 year old legacy of terror.